1960
DOI: 10.1149/1.2427886
|View full text |Cite
|
Sign up to set email alerts
|

The Electrolytic Formation and Dissolution of Oxide Films on Platinum

Abstract: The extent of surface oxidation of a smooth platinum electrode and the electrode capacitance were measured for various conditions of anodization. The electrolytic formation of the surface platinum oxide is shown to be a highly irreversible reaction. A mechanism which involves a hydroxyl radical intermediate of the oxygen evolution reaction is proposed for the surface oxide formation reaction. This mechanism is supported by the shapes of the anodic and cathodic charging curves on platinum and the interrelations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0

Year Published

1963
1963
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(112 citation statements)
references
References 16 publications
6
106
0
Order By: Relevance
“…62 The reduction of oxide to hydrogen peroxide, which is also suggested in the literature, 63 has not been confirmed 62 but cannot be completely excluded. In this view, the smaller reduction peak in the presence of [2-Sea + ][TfO − ] could either be due to the formation of a thinner oxide layer or only a partial reduction of PtO involving the formation of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 94%
“…62 The reduction of oxide to hydrogen peroxide, which is also suggested in the literature, 63 has not been confirmed 62 but cannot be completely excluded. In this view, the smaller reduction peak in the presence of [2-Sea + ][TfO − ] could either be due to the formation of a thinner oxide layer or only a partial reduction of PtO involving the formation of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 94%
“…This peak has been assigned to the oxidation of Pt to PtO. Based on the previous literature data 4,5,6,7,8,9 the three oxidation peaks of EtOH in Figure 11 were assigned as follows: 3 CHO to CH 3 COOH will also take place. The poisoning of the electrode occurs by the formation of PtO when the reaction A is faster than reaction B.…”
Section: Summary and Scopementioning
confidence: 84%
“…Measurements were not extended above 1. 8 v to avoid permanent damage to the electrode (1) resulting in part, perhaps, from extensive oxidation at the grain boundaries (11). A series of runs in which the time of anodization was varied showed that the charge obtained after 5 min.…”
Section: Reduction Curvesmentioning
confidence: 99%